1998
DOI: 10.1007/s11938-998-0002-1
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel dysmotility

Abstract: The most important initial step in treating patients with intestinal dysmotility is to exclude reversible causes, in particular mechanical obstruction. The presence or absence of bacterial overgrowth should be determined by small bowel aspirate or breath test, although an empiric trial with antibiotics is an appropriate alternative. Physicians should use agents effective against gram-negative organisms, such as broad-spectrum penicillins or tetracycline, particularly those that provide coverage of anaerobes, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Patients with dysmotility had intact bowel anatomy but often were unable to obtain sufficient nutrition by enteral feeding. However, even during PN, oral intake was still encouraged to promote use of the native intestine 23 . An earlier study on oral nutrition in HPN indicated that oral caloric intake in patients with SBS exceeded calculated resting energy expenditure and that patients with dysmotility consumed oral calories at 50% of their calculated resting energy expenditure 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with dysmotility had intact bowel anatomy but often were unable to obtain sufficient nutrition by enteral feeding. However, even during PN, oral intake was still encouraged to promote use of the native intestine 23 . An earlier study on oral nutrition in HPN indicated that oral caloric intake in patients with SBS exceeded calculated resting energy expenditure and that patients with dysmotility consumed oral calories at 50% of their calculated resting energy expenditure 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with underlying neuropathies or myopathies may also manifest symptoms of small-bowel dysmotility (1,4). These symptoms include abdominal pain, diarrhea, constipation, abdominal distension, bloating, nausea, or vomiting (2,3,5). Given these nonspecific symptoms, differentiating between upper-and lower-gastrointestinal-tract dysfunction in patients with suspected motility disorders can be challenging.…”
mentioning
confidence: 99%